1991
DOI: 10.1139/y91-084
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolism in older subjects using 31P magnetic resonance spectroscopy

Abstract: We used phosphorus magnetic resonance spectroscopy to study the calf muscles of elderly normal (mean +/- SD) (80.0 +/- 5.12 years), elderly impaired (80.7 +/- 0.58 years), old normal (66.8 +/- 1.92 years), and young normal people (24.6 +/- 4.72 years). Relative levels of inorganic phosphate (Pi), phosphocreatine (PCr), and adenosine triphosphate were measured with a 1.9-tesla, 30-cm bore magnet at rest and following plantra flexon exercise. No differences were found at rest or during recovery from exercise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 0 publications
6
36
4
Order By: Relevance
“…They are not consistent with the results of one in vivo study (McCully et al 1991) and two in vitro (enzyme activities) studies (Coggan et al 1992;Houmard et al 1998), all of which showed lower oxidative capacity in the O subjects. In the first study (McCully et al 1991), the lack of control for PA and health status of the O subjects likely contributed to lower oxidative capacity in that group. The discrepancy between the present results and those of the two in vitro studies is less clear, as both only studies included only people who reported that they were sedentary.…”
Section: Age and Oxidative Capacitycontrasting
confidence: 90%
See 3 more Smart Citations
“…They are not consistent with the results of one in vivo study (McCully et al 1991) and two in vitro (enzyme activities) studies (Coggan et al 1992;Houmard et al 1998), all of which showed lower oxidative capacity in the O subjects. In the first study (McCully et al 1991), the lack of control for PA and health status of the O subjects likely contributed to lower oxidative capacity in that group. The discrepancy between the present results and those of the two in vitro studies is less clear, as both only studies included only people who reported that they were sedentary.…”
Section: Age and Oxidative Capacitycontrasting
confidence: 90%
“…In contrast with studies of the TA, other studies have shown age-related declines in oxidative capacity of the plantarflexor muscles using both in vivo (McCully et al 1991) and in vitro approaches (e.g., enzyme activities; Coggan et al 1992;Houmard et al 1998). In the quadriceps muscles, which are most commonly studied, in vivo (Conley et al 2000;Larsen et al 2012b) and in vitro (Short et al 2005) oxidative capacities are both lower in O adults.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In humans, regional differences could result not only from regional differences in intramuscular pressure, but also from disease. Atherosclerosis can significantly reduce oxygen delivery to skeletal muscle [17][18][19][20], and the progression of atherosclerosis is unevenly distributed among conduit arteries [21]. Thus the development of a new noninvasive method for determining regional differences in oxygen status in humans is of great potential value.…”
mentioning
confidence: 99%